The quality function deployment and the theory of inventive problem solving: an approximation analysis for problem solving - Cruz-Rivero, Lidilia (2023)
The Quality Function Deployment (QFD) and the Theory of Inventive Problem Solving (TRIZ) are independent methodologies, that can be used and developed freely, but can be an important enhancer when you want to achieve innovation if they work together. The objective of this article is to present an analysis of the customers’ requirements in a product manufactured with biodegradable materials, the output result when applying the QFD was the quality critic related to toxicity, while the input information for the matrix TRIZ’s technical contradictions were the translation of the quality critic to one of the 39 technical design parameters, corresponding to parameter 30 (Harmful factors acting on the object from outside), being considered as the transfer point between the methodologies thus achieving the integration of both.